2014
DOI: 10.3810/pgm.2014.01.2721
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin for Cardioprotection and Strategies to Improve Patient Adherence

Abstract: Cardiovascular disease (CVD) is the leading cause of morbidity and mortality in North America. Aspirin therapy has proven clinical effectiveness in the prevention and treatment of CVD and is one of the most widely used drugs nationwide. However, despite the medication's popularity and utility, adherence to a proper aspirin regimen is suboptimal, resulting in adverse health outcomes and increased health care costs. Our review outlines current knowledge on aspirin therapy adherence, causes of nonadherence, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 81 publications
2
13
0
1
Order By: Relevance
“…Indeed, when we searched for predictors of low adherence to LDA, the absence of a secondary indication for LDA use was the main predictor of being in the noadherent or delayed not-adherent versus persistent adherent group. The probability of being in the not-adherent group was also increased with female sex, low socioeconomic status or polymedication, which agreed with other studies 17,20,37,38 , and was decreased with other covariates that are associated with an increased rate of cardiovascular diseases. Finally, dementia was also associated with good adherence, which suggests that these individuals are in an advanced stage and might be relying on caregivers to administer medications and thus show good adherence behavior 47 .…”
Section: Gbtm Underlined the Presence Of 4 Distinct Profiles Of Adhersupporting
confidence: 90%
See 1 more Smart Citation
“…Indeed, when we searched for predictors of low adherence to LDA, the absence of a secondary indication for LDA use was the main predictor of being in the noadherent or delayed not-adherent versus persistent adherent group. The probability of being in the not-adherent group was also increased with female sex, low socioeconomic status or polymedication, which agreed with other studies 17,20,37,38 , and was decreased with other covariates that are associated with an increased rate of cardiovascular diseases. Finally, dementia was also associated with good adherence, which suggests that these individuals are in an advanced stage and might be relying on caregivers to administer medications and thus show good adherence behavior 47 .…”
Section: Gbtm Underlined the Presence Of 4 Distinct Profiles Of Adhersupporting
confidence: 90%
“…Still, previous studies have shown that adherence to LDA is suboptimal 17,18 , with the lowest rates among all cardiovascular preventive therapies (65%) 17 . Consequences of this poor adherence are decreased treatment effectiveness and increased cardiovascular morbidity and mortality [19][20][21] . Poor adherence is complex, given its multifactorial nature 22 , and needs to be well understood and described to be better managed.…”
Section: Introductionmentioning
confidence: 99%
“…Duffy et al reported in their review that knowledge about aspirin and compliance were not optimal ranging between 72 and 92%. 25 Of the 12 included studies in this review, none of the studies were related to children. Specifically, in children, Lee and colleagues conducted a study among parents of 87 children waiting for organ transplantation.…”
Section: Knowledge About Aspirinmentioning
confidence: 99%
“…Despite these and numerous other studies showing the clinical efficacy of ASA use, clinical effectiveness is hindered substantially by underuse of these medications. Past studies have estimated ASA compliance to range from 72 to 92% [7] . Among patients who were prescribed ASA following hospitalization for an acute MI, patient adherence to the regimen was only 10% after 5 years, compared with 17% for statins, 31% for ACE inhibitors and 36% for β-blockers [8] .…”
Section: Overview and Unmet Needsmentioning
confidence: 99%